Effectiveness of cultural rights and the return of African cultural property acquired during the colonial era: bridging the gaps between texts and context (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This article draws on the annual theme of the African Union – ‘Arts, Culture and Heritage: Levers for Building the Africa We Want’ – to address the question related to the return or restitution of African cultural property irregularly acquiredduring the colonial and slavery regimes. It departs from the assumption that the African human rights system has a consistent normative and jurisprudential fabric on cultural rights. However, its main instruments ignore the issue of the return ofcultural property. This question finds a favourable response in a mixture of disparate texts – which regulate the cultural sector in general – whose institutional emanation is as multiple as it is diversified (African Union, UNESCO and United Nations General Assembly). The analysis of these texts allows us to establish a causal link between the return of African cultural goods and the effectiveness of cultural rights. This article puts forward the hypothesis according to which the return of these properties would not only be a mode of reparation for colonial crimes but above all a contribution to the effectiveness of cultural rights. Speaking of the obstacles that undermine the concretisation of the repatriation of the illegally acquired property, this article criticises the development of a certain artistic and cultural nationalism – consecutive to the fragmentary character of the state policies in the matter – generating innumerable impasses. As a palliative, the article advocates for the harmonisation of cultural policies at the regional level.